The impact of work-family conflict on Muslim women's well-being in selected Malaysian universities : the moderating role of religious coping strategy / Meguellati Achour - Achour, Meguellati (2012)
The purpose of this research is to investigate work-family satisfaction outlook in Malaysian academic institutions and the role of religious coping strategies for managing work demands and family roles to help Muslim working women to reach their potential in terms of productivity, commitment and achieve well-being. The determinants of well-being included under this research are job satisfaction, family satisfaction and life satisfaction. Under this overall purpose specific research objectives are: to what extent work-family demands and management/supervisory have direct effect on work-family conflict; to examine the role of moderating effect of religious coping strategies on the relationship between work-family conflict and well-being; to what extent religious coping strategies have direct relationship to well-being; to what extent religious coping strategies have strong relationship to work-family conflict; and determine the relationship between work-family conflicts on employees’ well-being? In this study the researcher has used random sampling method to obtain 315 samples from four universities in the Kelang Valley in Malaysia region and used questionnaires to collect the data. A survey was conducted among 315 Muslim working women, in Research Universities in the Klang Valley including University of Malaya, National University, Putra University, and international Islamic university, Kuala Lumpur, Malaysia. Their ages ranged from 30 to 60 years. The researcher, in this study used eight hypotheses to answer the research questions. The study’s results showed: Firstly, results that supervisory/ management support and religious coping strategies were positively and significantly associated with well-being. Work-family conflict and work-family demands are negatively and significantly related to well-being. Secondly, results from the study demonstrated that, work-family demands are positively and significantly related to work-family conflict. Supervisory/ management support has negative and significant relationship with work-family conflict, but religious coping strategies also have positive relationship with work-family conflict but not a significant. Thirdly, results from the study illustrated that, religious coping strategies as a moderator play a role in the relationship between work-family conflict and employees’ well-being. In conclusion, the main difference of coping strategies between Western and Islamic perspective is the emphasis among individual‟s relationships with its Creator and their reliance on Allah (SWT). This research provided Muslim women by some strategies to help them to manage the conflicting demands and family roles; furthermore, assist them in the reduction of anxiety, depression, work-family conflict, and restitution of hope.